Coronary CT Angiography in the Diagnosis of Coronary Artery Disease - Sun, Zhonghua; Wan, Yung-Liang; Hsieh, I-Chang; Liu, Yuan-Chang; Wen, Ming-Shien (Bentham Science Publishers, 2013)
Coronary CT angiography is increasingly used in the diagnosis of coronary artery disease due to rapid technological developments, which are reflected in the improved spatial and temporal resolution. High diagnostic accuracy has been achieved with 64- and more slice CT scanners, and in selected patients, coronary CT angiography is considered a reliable alternative to invasive coronary angiography. Quantifying the amount of coronary artery calcium with coronary CT angiography has been widely accepted as a reliable non-invasive technique for predicting risk of future cardiac events. Coronary CT angiography is able to detect variable densities in the coronary atherosclerotic plaques and demonstrate the corresponding intraluminal changes due to presence of plaques, thus providing prognostic value of disease extent. Coronary CT angiography is an accurate method to measure coronary bifurcation angles and demonstrate dimensional changes, hence, providing relevant features of left coronary atherosclerosis. This article provides an overview of the diagnostic and predictive value of coronary CT angiography in coronary artery disease.